Agriculture beckons digital transformation - Dadhich, Balendu Sharma (Kurukshetra: A Journal on Rural Development)
This decode could be the best time for a digital revolution of Indian agricultural for a multitude of factors including the futuristic vision for agricultural of the opex level in the government of India.- Reproduced